2003
DOI: 10.1002/app.11879
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization kinetics and melting behavior of nylon 10,10 in nylon 10,10–montmorillonite nanocomposites

Abstract: ABSTRACT:The crystallization kinetics and melting behavior of nylon 10,10 in neat nylon 10,10 and in nylon 10,10 -montmorillonite (MMT) nanocomposites were systematically investigated by differential scanning calorimetry. The crystallization kinetics results show that the addition of MMT facilitated the crystallization of nylon 10,10 as a heterophase nucleating agent; however, when the content of MMT was high, the physical hindrance of MMT layers to the motion of nylon 10,10 chains retarded the crystallization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
37
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 25 publications
4
37
0
Order By: Relevance
“…The investigation of PLLA/organoclay composites exhibited a similar lower cold crystallization temperature phenomenon compared to that of pure PLLA. [18] Zhang et al [18] attributed this to the nucleating effect of well-dispersed organoclay layers. Therefore, HGBs are expected to act as efficient nucleating agents.…”
Section: Resultsmentioning
confidence: 99%
“…The investigation of PLLA/organoclay composites exhibited a similar lower cold crystallization temperature phenomenon compared to that of pure PLLA. [18] Zhang et al [18] attributed this to the nucleating effect of well-dispersed organoclay layers. Therefore, HGBs are expected to act as efficient nucleating agents.…”
Section: Resultsmentioning
confidence: 99%
“…Sanchez-Garcia et al (2008) also mentioned the transcrystallinity effect, whereby the fibers can cause crystal nucleation of the biopolymers. Also, in previous study (Zhang & Yan, 2003), they added cellulose nanowhiskers (CNW) as a reinforcing element to PLA nanocomposites. They revealed that the crystallinity increased with the addition of CNW could be explained by the fiber-induced crystallization of the biopolymers.…”
Section: Differential Scanning Calorimetry (Dsc)mentioning
confidence: 99%
“…This behaviour is in contrast to the work by Peterson but agrees with a previous work in PHBV (Jiang et al 2008). The crystallinity increase with the addition of CNW has been explained by the assumption that the CNW act as efficient nucleating agents, which enhance the crystallization rate of the matrix molecules (Zhang and Yan 2003). In principle, fillerinduced crystallization of the biopolymers, particularly transcrystallinity that blocks the filler matrix interface, is positive from a barrier perspective, since crystals are typically impermeable systems.…”
Section: Thermal Propertiesmentioning
confidence: 99%